Risk Theory as a Basis for International Responsibility for The Unilateral Exploitation of Joint Oil Fields - Ayobe, Maha Mohammed; Uloom, Ibrahim Bahr Al; Wahhab, Ali Abdulhussein (Indonesian Journal of Law and Economics Review, 2025)
General Background: The exploitation of cross-border natural resources, particularly oil fields, poses intricate challenges in the realm of public international law. Specific Background: While the principle of permanent sovereignty grants states the right to utilize resources within their territories, complexities arise when these resources span multiple jurisdictions. Knowledge Gap: Current legal discourse lacks comprehensive analysis on the basis of international responsibility for unilateral actions within such joint resource zones. Aim: This research investigates the international legal foundations for state responsibility in the unilateral exploitation of shared oil fields. Results: The study demonstrates that although a state may act within its sovereign rights, unilateral exploitation can cause transboundary damage, thereby invoking international responsibility grounded not on fault, but on harm caused. Novelty: The research introduces risk theory as a legitimate basis for attributing international responsibility, even in the absence of unlawful conduct, emphasizing damage and causation over intent. Implications: This approach promotes equitable resource governance and offers a legal framework to mediate disputes between states sharing oil reserves, reinforcing international cooperation and environmental justice principles. Highlights: Defines state responsibility for exploiting transboundary oil fields. Introduces risk theory as a legal basis beyond fault. Emphasizes equitable and cooperative resource management. Keywords: Permanent Sovereignty, Unilateral Exploitation, Joint Oil Fields, International Responsibility, Risk Theory